Percepção de usuários do Sistema Único de Saúde acerca do Programa Mais Médicos em um município do interior do Ceará (Brazilian Journal of Health Research, 2018)
Perception of users of the Brazilian National Health System (SUS) about the “Mais Médicos” (More Physicians) Program in a municipality in the countryside of Ceará, Brazil